Hilary Putnam - Ben-Menahem, Yemima, 1946- (Contemporary philosophy in focus., 2005)
The essays in this volume discuss Putnam's major philosophical contributions to the theory of meaning, the philosophy of mind, the philosophy of science and mathematics, and moral theory. The volume also constitutes a critical introduction to a number of central issues in contemporary philosophy.